Antithrombotic strategies for patients with coronary and lower extremity peripheral artery diseases: a narrative review. (1st December 2020) - De Luca, Leonardo; Bonaca, Marc P.; Magnani, Giulia
ABSTRACT: Introduction: Patients with coexisting coronary artery disease (CAD) and peripheral artery disease (PAD) present a very high rate of cardiovascular (CV) morbidity and mortality. Several studies have demonstrated that different regimens of antithrombotic therapies may reduce adverse CV events in patients with CAD or PAD. However, data on optimal antithrombotic combination to use in these very high-risk patients are scarce and conflicting. Areas covered: This paper reviews current data on antithrombotic therapies tested in CAD patients with concomitant lower extremity PAD. Expert opinion: The antithrombotic response in lower extremity PAD patients varies based on the atherosclerotic burden. For patients with isolated stable PAD may be sufficient a less potent P2Y12 inhibitor as clopidogrel, whereas patients with lower extremity PAD and documented CAD benefit from a more intense and prolonged antithrombotic treatment.